Development and validation of a nutritional literacy assessment scale for nasopharyngeal carcinoma patients undergoing concurrent chemoradiotherapy - Yanxin, Zhang; Xiaojun, Huang; Guirong, Yang; Wei, Li; Limin, Liang; Lina, Wei; Jiamei, Lu (Frontiers in Nutrition, 2025)
BackgroundNasopharyngeal carcinoma (NPC) is a head and neck malignancy highly prevalent in East and Southeast Asia, for which concurrent chemoradiotherapy (CCRT) is the standard treatment option. However, the superimposed effects of radiotherapy (especially head and neck radiotherapy) and chemotherapy often lead to severe acute toxic reactions, insufficient nutritional knowledge of patients, and dietary misconceptions all affect the patient’s ability to eat and their nutritional status. Therefore, there is an urgent need to develop a Nutritional Literacy Scale (NLS) for patients undergoing simultaneous radiotherapy and chemotherapy for nasopharyngeal carcinoma (NPC) to optimize the overall nutritional management of NPC patients and to improve the therapeutic effect.MethodsThe first draft of the scale was formed through literature analysis, semi-structured interviews, and expert correspondence. From April 2024 to December 2024, 245 patients with nasopharyngeal carcinoma treated with simultaneous radiotherapy and chemotherapy in the radiotherapy department of the First Affiliated Hospital of Guangxi Medical University were collected as the study subjects, and the scale was subjected to item analysis and reliability and validity tests, and the questionnaire was administered again to the patients 2 weeks later to measure the re-test reliability of the scale.ResultsThe Nutritional Literacy Scale for Nasopharyngeal Carcinoma Patients Undergoing Simultaneous Radiotherapy included 4 dimensions and 30 entries. Exploratory factor analysis extracted four male factors with a cumulative variance contribution of 62.3%; validated factor analysis showed that χ2/df = 1.155 (p = 0.085), GFI = 0.928, RMSEA = 0.025, CFI = 0.994, NFI = 0.956, and IFI = 0.994; questionnaire content validity I-CVI was 0.872 to 1.000, S-CVI was 0.932; Cronbach’s alpha coefficient for the total scale was 0.849, folded reliability was 0.869, and retest reliability was 0.960.ConclusionThe Nutritional Literacy Scale for Nasopharyngeal Cancer Patients Undergoing Simultaneous Radiotherapy has good reliability and validity.